La información como derecho: entornos virtuales como posibilitadores y profesor como garante - Serra, Silvana; Brizuela, Mónica; Serra, Mariel; Beltramone, Diego Antonio; Soria, Elio Andrés (Universidad Nacional de Córdoba, 2020)
11 p.